2017
DOI: 10.1371/journal.pone.0183206
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality affects dietary diversity of school-age children in northern Ghana

Abstract: Background and objectivesDietary diversity score (DDS) is relatively easy to measure and is shown to be a very useful indicator of the probability of adequate micronutrient intake. Dietary diversity, however, is usually assessed during a single period and little is known about the effect of seasonality on it. This study investigates whether dietary diversity is influenced by seasonality.MethodsTwo cross-sectional surveys were conducted in two different seasons—dry season (October 2010) and rainy season (May 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
52
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 56 publications
6
52
1
1
Order By: Relevance
“…Considering that our study population was rural with a general low socio-economic status reflected in their poor educational and occupational status, we assumed fruit consumption may be scarce and may also not differ between the women in fertile age. For instance, a recent study that examined the effect of seasonality on the dietary diversity of school-aged children in the study area found that the consumption of vitamin C-rich fruits was less than 2% in both the dry and raining seasons; in this study, the consumption of vitamin A-rich fruits was significantly higher in the rainy season compared to the dry season (64% vs 0.9%, P  = < 0.001), but was in part attributed the consumption of wild shea fruits ( Butyrospermum Parkii ) and mangoes, available only in the early part of the rainy season [40]. Overall, considering the lower fruit consumption and the seasonality association with it, vegetable intake perhaps remained the most critical exposure for the sampled population.…”
Section: Discussionmentioning
confidence: 72%
“…Considering that our study population was rural with a general low socio-economic status reflected in their poor educational and occupational status, we assumed fruit consumption may be scarce and may also not differ between the women in fertile age. For instance, a recent study that examined the effect of seasonality on the dietary diversity of school-aged children in the study area found that the consumption of vitamin C-rich fruits was less than 2% in both the dry and raining seasons; in this study, the consumption of vitamin A-rich fruits was significantly higher in the rainy season compared to the dry season (64% vs 0.9%, P  = < 0.001), but was in part attributed the consumption of wild shea fruits ( Butyrospermum Parkii ) and mangoes, available only in the early part of the rainy season [40]. Overall, considering the lower fruit consumption and the seasonality association with it, vegetable intake perhaps remained the most critical exposure for the sampled population.…”
Section: Discussionmentioning
confidence: 72%
“…Finally, the observed seasonal variations in micronutrient status were in part attributed to seasonal variation in the availability and access to food, notably, the micronutrient‐rich food. Several studies have indeed shown seasonality variations in dietary intake . The implication of the finding may be that interventions that aim to improve the nutritional status of adolescents in the context of LMICs need to recognize the role of seasonality on nutritional status to incorporate initiatives to prevent undesirable seasonal declines in nutrient intake and consequently nutritional status.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indeed shown seasonality variations in dietary intake. [163][164][165][166] The implication of the finding may be that interventions that aim to improve the nutritional status of adolescents in the context of LMICs need to recognize the role of seasonality on nutritional status to incorporate initiatives to prevent undesirable seasonal declines in nutrient intake and consequently nutritional status.…”
Section: Environment and Communitymentioning
confidence: 99%
“…Importantly, we find statistically and economically significant association between the consumption of meats and poultry, as well as milk and milk products, with households' access to irrigation. Underconsumption of animal-source-foods is common in Ghana across seasons, pointing to a high risk of micronutrient inadequacy, especially for vulnerable sub-populations like school-aged children (Abizari et al, 2017;Colecraft et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…A study on school-aged children in Northern Ghana showed seasonal variations in dietary diversity, where dietary diversity was higher in the rainy season due to increased consumption of fruits and vegetables compared to the dry season (Abizari et al, 2017).…”
Section: Discussionmentioning
confidence: 99%